ULF Pc5‐6 magnetic activity in the polar cap as observed along a geomagnetic meridian in Antarctica - Yagova, N. V.; Lanzerotti, L. J.; Villante, U.; Pilipenko, V. A.; Lepidi, S.; Francia, P.; Papitashvili, V. O.; Rodger, A. S. (Journal of Geophysical Research: Space Physics, 2002)
Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/94669/1/jgra16442.pdf